A register-based account of period trends in partnership prevalence, entries, and exits by educational level for men and women in Finland - Jalovaara Marika; Andersson Linus (Turun yliopisto, 2022)
BACKGROUND The decline in marriage and increase in cohabiting unions represent a major change in family and fertility dynamics. Yet, no comprehensive description has covered period trends in the prevalence of marital and non-marital partnerships, or partnership entry and exit rates, across educational levels.
OBJECTIVE We describe period trends in the proportion of partnered individuals and the flow of partnership formation and dissolution at ages 18–49 across educational levels for men and women in 1989–2019 in Finland.
METHODS We use total-population register data that include full histories of co-residential partnerships regardless of marital status. We calculate the age-specific yearly prevalence of marriages, cohabitations, and all unions; and rates of union formation (among non-partnered population) and rates of separation (among the partnered population).
RESULTS The prevalence of marriage declined across educational groups. Increases in the prevalence of cohabitation are slightly smaller than declines in marriage; as a result, the total prevalence of partnerships declined, especially among low-educated men and women. Union formation rates have declined recently, and separation rates have increased notably, but more so among the lower educated and in age groups below 35.
CONCLUSIONS The increase of non-marital cohabitation has not fully covered for the decline in marriage. Increases in partnership instability are notable. All partnership trends and the educational gradients are remarkably similar among men and women in Finland.
CONTRIBUTION We provide the first comprehensive population-level estimates of trends and patterns of the partnership stock and flows of marital and non-marital partnerships by education for both men and women.